Plant-based cellulose fiber as biomaterials for biomedical application: A Short Review - Azril Azril; Yeau-Ren Jeng; Agus Nugroho (Journal of Fibers and Polymer Composites, 2023)
Cellulose is the most common polysaccharide that can be obtained from many resources. Plant-based cellulose (PC) is preferable due to its high renewability and availability in nature. This inherent affluence naturally opens the door to new applications for this adaptable material. PC provides various potential applications such as packaging, textile, and biomedical application. Currently, PC shows progress in its feasibility in biomedical applications because it fulfills the requirement of the characteristics of biomaterials such as biocompatible, biodegradable, anti-microbial, and enhancing tissue regeneration. Different morphological forms of PC such as fiber, microfibril/nanofibril cellulose (MFCs/NFCs), and micro/nanocrystalline cellulose (MCCs/NCCs) are adapted for different biomedical applications. This short review provides a general characteristic of plant-based cellulose (PC) and its potential to be applied in biomedical fields such as tissue engineering.